Lower Number of Teeth Is Related to Higher Risks for ACVD and Death—Systematic Review and Meta-Analyses of Survival Data - Beukers, Nicky G. F. M.; Su, Naichuan; Loos, Bruno G.; van der Heijden, Geert J. M. G. (Frontiers in Cardiovascular Medicine, 2021)
Tooth loss reflects the endpoint of two major dental diseases: dental caries and periodontitis. These comprise 2% of the global burden of human diseases. A lower number of teeth has been associated with various systemic diseases, in particular atherosclerotic cardiovascular diseases (ACVD). The aim was to summarize the evidence of tooth loss related to the risk for ACVD or death. Cohort studies with prospective follow-up data were retrieved from Medline-PubMed and EMBASE. Following the PRISMA-guidelines, two reviewers independently selected articles, assessed risk of bias and extracted data on number of teeth (tooth loss; exposure) and ACVD-related events and all-cause mortality (ACM) (outcome). In total 75 articles were included of which 44 qualified for meta-analysis. A lower number of teeth was related to a higher outcome risk; the pooled Risk Ratio (RR) for cumulative incidence of ACVD ranged from 1.69 to 2.93, and for cumulative incidence of ACM the RR ranged from 1.76 to 2.27. The pooled multiple adjusted Hazard Ratio (HR) for incidence density of ACVD ranged from 1.02 to 1.21 and for incidence density of ACM the HR ranged from 1.02 to 1.30. This systematic review and meta-analyses of survival data shows that a lower number of teeth is a risk factor for both ACVD and death. Health care professionals should use this information to inform their patients and increase awareness on the importance of good dental health and to increase efforts to prevent tooth loss.